Functional Disorders Of The Digestive Organs In Children Of Early Age. Intestinal Colic (Progress Annals: Journal of Progressive Research, 2024)
The goal is to focus the attention of doctors in medical practice on intestinal colic, which is common in children of early age, to increase their knowledge in this area by introducing them more broadly. The article describes intestinal colic, reveals its epidemiology, classification, etiology, pathogenetic factors, clinical appearance, diagnosis, differential dagnostics based on Roman criteria and modern recommendations, and provides dietary treatments, healing Milky mixtures and other treatments.